2015
DOI: 10.1164/rccm.201410-1876pp
|View full text |Cite
|
Sign up to set email alerts
|

Blue Journal Conference. Aging and Susceptibility to Lung Disease

Abstract: The aging of the population in the United States and throughout the developed world has increased morbidity and mortality attributable to lung disease, while the morbidity and mortality from other prevalent diseases has declined or remained stable. Recognizing the importance of aging in the development of lung disease, the American Thoracic Society (ATS) highlighted this topic as a core theme for the 2014 annual meeting. The relationship between aging and lung disease was discussed in several oral symposiums a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 108 publications
(115 reference statements)
3
132
0
3
Order By: Relevance
“…The incidence of IPF increases more than fivefold when comparing adults 45 to 54 years of age with those >75 years of age. 84 Recent reviews in aging biology have identified specific biological processes that are altered in aging, and several have been associated with human pulmonary fibrosis disorders, including genomic instability, telomere erosion, epigenetic changes, proteostasis, and cellular senescence. 85 Several investigators demonstrate that aged fibroblasts are profibrotic.…”
Section: Role Of Senescence and Aging In Removing Myofibroblastsmentioning
confidence: 99%
“…The incidence of IPF increases more than fivefold when comparing adults 45 to 54 years of age with those >75 years of age. 84 Recent reviews in aging biology have identified specific biological processes that are altered in aging, and several have been associated with human pulmonary fibrosis disorders, including genomic instability, telomere erosion, epigenetic changes, proteostasis, and cellular senescence. 85 Several investigators demonstrate that aged fibroblasts are profibrotic.…”
Section: Role Of Senescence and Aging In Removing Myofibroblastsmentioning
confidence: 99%
“…MIF and chronic obstructive pulmonary disease. COPD is the third leading cause of death in the United States and occurs predominately among individuals greater than 45 years of age (112,140). COPD is associated with an increase in cellular senescence, DNA damage, and oxidative stress (5,144,157,161).…”
Section: Mif In Animal Models and Human Studies Of Age-related Lung Dmentioning
confidence: 99%
“…Pneumonia and dementia are major concerns as societies age worldwide [1,2]. They frequently coexist [3]; pneumonia is the most common cause of death in patients with dementia [4,5], and dementia is a well-recognized risk factor for community acquired pneumonia [6] and aspiration pneumonia [7] in the elderly.…”
Section: Introductionmentioning
confidence: 99%